Diurnal, monthly and seasonal variation of mean winds in the MLT region observed over Kolhapur using MF radar. (April 2018) - Sharma, A.K.; Gaikwad, H.P.; Ratnam, M. Venkat; Gurav, O.B.; Ramanjaneyulu, L.; Chavan, G.A.; Sathishkumar, S.
Abstract: Medium Frequency (MF) radar located at Kolhapur (16.8°N, 74.2°E) has been upgraded in August 2013. Since then continuous measurements of zonal and meridional winds are obtained covering larger altitudes from the Mesosphere and Lower Thermosphere (MLT) region. Diurnal, monthly and seasonal variation of these mean winds is presented in this study using four years (2013–2017) of observations. The percentage occurrence of radar echoes show maximum between 80 and 105 km. The mean meridional wind shows Annual Oscillation (AO) between 80 and 90 km altitudes with pole-ward motion during December solstice and equatorial motion during June solstice. Quasi-biennial oscillation (QBO) with weaker amplitudes are also observed between 90 and 104 km. Zonal winds show semi-annual oscillation (SAO) with westward winds during equinoxes and eastward winds during solstices between 80 and 90 km. AO with eastward winds during December solstice and westward wind in the June solstice is also observed in the mean zonal wind between 100 and 110 km. These results match well with that reported from other latitudes within Indian region between 80 and 90 km. However, above 90 km the results presented here provide true mean background winds for the first time over Indian low latitude region as the present station is away from equatorial electro-jet and are not contaminated by ionospheric processes. Further, the results presented earlier with an old version of this radar are found contaminated due to unknown reasons and are corrected in the present work. This upgraded MF radar together with other MLT radars in the Indian region forms unique network to investigate the vertical and lateral coupling. Highlights: Mean winds in the MLT region is presented using four years of observations from upgraded MF radar located at Kolhapur. Above 90 km, this radar provides true mean background neutral winds for the first time over Indian low latitude region. Results presented earlier with an old version of this radar are found contaminated due to unknown reasons and are corrected. This radar along with other MLT radars in the Indian region forms unique network for vertical and lateral coupling studies.